Temperature dependence of the nucleation effect of sorbitol derivatives on polypropylene crystallization - Kim, C.Y.; Kim, Y.C.; Kim, S.C. (1993)
The temperature dependence of the nucleation effect of three sorbitol derivatives on the crystallization of isotactic polypropylene (iPP) was studied by means of isothermal crystallization kinetic analysis. Isothermal crystallization thermograms obtained by differential scanning calorimetry (DSC) were analyzed based on the Avrami equation. The Avrami analysis for the nucleated iPP was carried out with DSC data collected to 35% relative crystallinity, and the rate constants were corrected assuming the heterogeneous nucleation and three dimensional growth of iPP spherulites. A semiempirical equation for the radial growth rate of iPP spherulites was given as a function of temperature and was used to determine the number of effective nuclei at different temperatures. The number of effective nuclei in the nucleated samples was estimated to be 3 × 102 ∽ 105 times larger than that in the neat iPP. The logarithmic numbers of the effective nuclei decreased linearly with decreasing degree of supercooling in the range of crystallization temperatures tested. The temperature dependence of the effect of the nucleating agents on iPP crystallization was given quantitatively in terms of the deactivation factor defined as a fraction of the particles that are active at a particular temperature but inert at the temperature one degree higher. The nucleation activity and its temperature dependence are considered to be cooperative effects of many factors, including the dispersion and the physical or chemical nature of the agent as well as the interaction between the agent and the polymer. It is suggested that the temperature dependence of the effect of a nucleating agent should be treated as a characteristic of a given polymer/ nucleating agent mixture. Copyright ？ 1993 Society of Plastics Engineers
Keywords: Calorimetry; Crystallization; Thermal effects; Avrami equation; Differential scanning calorimetry; Nucleation; Sorbitol derivatives; Polypropylenes